Pregnancy and Healthy Childbirth in a 37 Year-Old Patient with Diverticular Disease - P. S. Andreev; S. E. Katorkin; O. E. Davydova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2020)
Aim. To describe a clinical case of pregnancy and healthy labour in a young female patient with uncomplicated diverticular disease (DD).Key points. In recent years, DD is more frequently observed in younger patients. A 37-yo woman manifested the symptoms of periodic intense abdominal pain and constant abdominal discomfort. Colonic DD was diagnosed with irrigoscopy. A high-fibre diet, rifaximin-α at 400 mg twice a day for one week, once a month for six months, and topical anti-inflammatory therapy were prescribed. Clinical symptoms were eradicated upon the treatment. Unaware of pregnancy, the patient had another course of rifaximin-α at the second week of gestation, after which the therapy was stopped. Rifaximin-α, which has a poor intestinal absorption, did not affect the foetal development. A caesarean childbirth was healthy, the newborn was delivered on term with no complications (Apgar score 8).Conclusion. DD should be included in differential diagnosis for patients with non-specific symptoms (abdominal pain, bloating and discomfort), regardless of young age. No protocols are currently accepted for the DD management during gestation. In the clinical case reported, a patient having diverticular disease and a rifaximin-α therapy at an early term of gestation proceeded without complications for herself and the foetus.